1982
DOI: 10.1111/j.1445-5994.1982.tb02457.x
|View full text |Cite
|
Sign up to set email alerts
|

Congestive Cardiomyopathy and Haemochromatosis- Rapid Progression Possibly Accelerated by Excessive Ingestion of Ascorbic Acid

Abstract: We describe rapidly fatal cardiomyopathy in a young man. He had for twelve months ingested large amounts of ascorbic acid and was admitted with severe heart failure having been symptomatic for two months. He died after eight days. Idiopathic haemochromatosis was diagnosed at autopsy. The clinical and laboratory features are discussed and the possible implications of ascorbic acid ingestion are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 8 publications
0
30
0
1
Order By: Relevance
“…This seems to be so in patients with idiopathic haemochromatosis and dietary iron overload ; indeed, supplementation of their diet with AA was reported to cause serious complications resulting from additional oxidative damage [38]. As final note, an in-hospital depletion-repletion study performed in human volunteers has revealed that AA supplementation promotes a prompt increase in the vitamin content of white blood cells [39].…”
Section: Resultsmentioning
confidence: 99%
“…This seems to be so in patients with idiopathic haemochromatosis and dietary iron overload ; indeed, supplementation of their diet with AA was reported to cause serious complications resulting from additional oxidative damage [38]. As final note, an in-hospital depletion-repletion study performed in human volunteers has revealed that AA supplementation promotes a prompt increase in the vitamin content of white blood cells [39].…”
Section: Resultsmentioning
confidence: 99%
“…Although AA-mediated Fenton reactions may be controlled in the plasma and lymph of healthy individuals by efficient iron sequestration in transferrin [21,22], the redox-active NTBI found in the serum of individuals with iron overload may catalyse free radical formation in the presence of AA. AA supplements were reported to enhance cell and organ damage, and eventually cause cardiac failure, in patients with iron overload [23][24][25]. Additionally, the formation of hydroxyl radicals from H 2 O 2 may occur intracellularly due to the presence of a pool of labile iron.…”
Section: Introductionmentioning
confidence: 99%
“…However, in humans, antioxidant therapy has not been shown to slow the progression of atherosclerotic coronary artery disease (7)(8)(9). On the contrary, several prospective angiographic studies have demonstrated that antioxidant therapy may be associated with a more rapid progression of atherosclerosis, potentially due to a deleterious effect on the lipid profile (8,10,11) or perhaps the ability of these antioxidants to become pro-oxidants under certain conditions (12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%